PENGARUH PEMBAGIAN TUGAS DAN WEWENANG TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN BADUNG - Komang Ayu Mita Pratiwi; I Dewa Nyoman Usadha; Putu Ari Mulyani (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of the division of tasks and authority on employee performance at the Badung Regency Human Resources and Development Agency. This study uses a quantitative method by distributing questionnaires to 81 respondents who are employees of the Badung Regency Human Resources and Development Agency. The data analysis technique used is multiple linear regression analysis. The results show that the division of tasks has a t-value of 5.581 with a significance value of 0.000, having a positive and significant effect on employee performance. Authority has a t-value of 5.778 with a significance value of 0.000, which has a positive and significant effect on employee performance. The F-value is 163.547, with a significance level of 0.000, indicating a value less than 0.05. Therefore, the division of tasks and authority has a positive and significant effect, both partially and simultaneously, on employee performance at the Badung Regency Personnel and Human Resource Development Agency. The implication of this study is that the leadership of the Badung Regency Personnel and Human Resource Development Agency must be able to implement an effective division of tasks among its employees and implement appropriate delegation of authority to them. Division of tasks can improve employee performance by allowing employees to focus on specific tasks and develop necessary skills. Clear and structured authority can increase efficiency by enabling employees to make decisions and take appropriate actions.